’’اجتماعی اجتہاد‘‘ کی اہمیت قرآن وسنت کی روشنی میں : The importance of Collective Ijtihad in the Light of the Quran and Sunnah - Siddique Ullah, Muhammad; Khalid Shafi, Dr.Hafiz Muhammad; Ali, Muhammad (Journal of Quranic and Social Studies, 2023)
Collective Ijtihad Is an Organized and Social Effort to Deliberate and Contemplate on Emerging Issues in The Islamic World, Seeking Their Legal Solutions Through Systematic and Collective Endeavors. The Consensus Achieved in Collective Ijtihad Results from Collective Consultation, Which Is Conducted Through the Gatherings of Islamic Jurisprudence (Fiqh) Scholars and Experts. In These Gatherings, Scholars Engage in Discussions and Analyse of Contemporary Issues and Strive to Find Their Legal Resolutions. Regard The Importance of Collective Ijtihad in Islam, Its Significance can be Traced Back to The Time of The Prophet Muhammad (Peace Be Upon Him) and the Era of The Rightly Guided Caliphs. The Quranic Injunction Emphasizing Consultation (Shura) and Social Deliberation Is Prominent in Islamic Governance and Politics. Islam Encourages Muslim Rulers To Engage in Consultation With Their Subjects on Various Social Matters, as Evidenced By The Quranic Verse That Highlights The Importance of Mutual Consultation (Shura)” امر هم شوری بینهم“Among Them. This Principle of Consultation Is Not Limited to Religious Matters but Is Also Applicable to Political, Social, And Administrative Affairs. Thus, Islamic Governance Encourages Consultation and Social Deliberation, and It Provides a Foundation for The Legitimacy of Collective Ijtihad. The Concept of Shura, as Exemplified in Islamic Governance, Supports the Notion of Collective Ijtihad, and Justifies its Place in Islamic Jurisprudence.